The Influence of Entrepreneurship Education, Practical Skills, and Digital Literacy on Entrepreneurial Intention and Entrepreneurial Success: The Influence of Entrepreneurship Education, Practical Skills, and Digital Literacy on Entrepreneurial Intention and Entrepreneurial Success - Ulfah, Fadilla; Wulandari, Riri; Yolanda, Yola; Rayana Siregar, Dwi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2026)
This study aims to analyze the influence of entrepreneurship education, practical skills, and digital literacy on students’ entrepreneurial intention and entrepreneurial success. This research employs a quantitative approach using the path analysis method. The sample consists of students selected through a specific sampling technique, with a total of 82 respondents. Data were collected through questionnaires and analyzed using SPSS. The results indicate that entrepreneurship education has a negative and insignificant effect on entrepreneurial success, while practical skills and digital literacy have a positive effect on entrepreneurial success. Furthermore, entrepreneurship education, practical skills, and digital literacy have a positive influence on entrepreneurial intention. However, entrepreneurial intention does not have a significant effect on entrepreneurial success. Simultaneously, entrepreneurship education, practical skills, digital literacy, and entrepreneurial intention influence entrepreneurial success. These findings suggest that students’ entrepreneurial success is more strongly influenced by practical skills and digital literacy than by entrepreneurship education and entrepreneurial intention alone. Therefore, it is necessary to enhance practice-based learning and strengthen digital literacy within entrepreneurship education to improve students’ entrepreneurial success.